The ADF/Cofilin-Pathway and Actin Dynamics in Podocyte Injury - Beina Teng; Alexander Lukasz; Mario Schiffer (International Journal of Cell Biology)
ADF/cofilins are the major regulators of actin dynamics in mammalian cells. The activation of ADF/cofilins is controlled by a variety of regulatory mechanisms. Dysregulation of ADF/cofilin may result in loss of a precisely organized actin cytoskeletal architecture and can reduce podocyte migration and motility. Recent studies suggest that cofilin-1 can be regulated through several extracellular signals and slit diaphragm proteins. Cofilin knockdown and knockout animal models show dysfunction of glomerular barrier and filtration with foot process effacement and loss of secondary foot processes. This indicates that cofilin-1 is necessary for modulating actin dynamics in podocytes. Podocyte alterations in actin architecture may initiate or aid the progression of a large variety of glomerular diseases, and cofilin activity is required for reorganization of an intact filtration barrier. Since almost all proteinuric diseases result from a similar phenotype with effacement of the foot processes, we propose that cofilin-1 is at the centre stage of the development of proteinuria and thus may be an attractive drug target for antiproteinuric treatment strategies.